Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Leonard Herr, Justice Stanley Mosk speaking at lectern, Fresno County Young Lawyers Association President John McGregor Star Palace lectern on table